2017
DOI: 10.1002/epi4.12041
|View full text |Cite
|
Sign up to set email alerts
|

Seven tesla MRI improves detection of focal cortical dysplasia in patients with refractory focal epilepsy

Abstract: SummaryObjectiveThe aim of this study is to determine whether the use of 7 tesla (T) MRI in clinical practice leads to higher detection rates of focal cortical dysplasias in possible candidates for epilepsy surgery.MethodsIn our center patients are referred for 7 T MRI if lesional focal epilepsy is suspected, but no abnormalities are detected at one or more previous, sufficient‐quality lower‐field MRI scans, acquired with a dedicated epilepsy protocol, or when concealed pathology is suspected in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 33 publications
3
62
0
Order By: Relevance
“…Consequently, patients have worse surgical outcomes compared to cases with visible lesions on MRI (Tellez‐Zenteno, Hernandez Ronquillo, Moien‐Afshari, & Wiebe, ). Technical advances of the static magnetic fields from 1.5 to 3 T and higher field strengths of 7 T can aid in detecting epileptogenic lesions that are otherwise difficult to perceive (De Ciantis et al, ; Knake et al, ; Veersema et al, ; Zijlmans et al, ). Also, computational methods have been shown helpful in detecting subtle lesions, previously missed in the visual analysis (Kotikalapudi et al, ; Martin, Bender, & Focke, ; Martin et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, patients have worse surgical outcomes compared to cases with visible lesions on MRI (Tellez‐Zenteno, Hernandez Ronquillo, Moien‐Afshari, & Wiebe, ). Technical advances of the static magnetic fields from 1.5 to 3 T and higher field strengths of 7 T can aid in detecting epileptogenic lesions that are otherwise difficult to perceive (De Ciantis et al, ; Knake et al, ; Veersema et al, ; Zijlmans et al, ). Also, computational methods have been shown helpful in detecting subtle lesions, previously missed in the visual analysis (Kotikalapudi et al, ; Martin, Bender, & Focke, ; Martin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Technical advances of the static magnetic fields from 1.5 to 3 T and higher field strengths of 7 T can aid in detecting epileptogenic lesions that are otherwise difficult to perceive (De Ciantis et al, 2016;Knake et al, 2005;Veersema et al, 2017;Zijlmans et al, 2009). Also, computational methods have been shown helpful in detecting subtle lesions, previously missed in the visual analysis Martin, Bender, & Focke, 2015;Martin et al, 2017).…”
mentioning
confidence: 99%
“…In the remaining subgroup of 15 patients with known lesions, MRI at 3T allowed for better delineation in 33% . Veersema et al in a series of 40 patients at 7T MRI identified additional lesions in 23% of patients not seen at 1.5 and 3T. The data suggest that higher magnetic field MRI has great potential to identify and better characterize inconspicuous epileptogenic lesions.…”
Section: Introductionmentioning
confidence: 94%
“…Over the past few years, ultra‐high‐field (UHF) 7T MRI machines have been available in a few research centers for in vivo human brain imaging. The increased signal‐to‐noise ratio, improved spatial structural resolution, and enhanced image contrast allow for better depiction, characterization, and visualization of millimetric anatomical structures and lesions such as FCD than 3T that offers the chance to reveal new features of neurological diseases that may change clinical diagnosis . Among sequences specifically designed for higher magnetic fields, magnetization‐prepared two rapid acquisition gradient echoes (MP2RAGE) is a 3‐dimensional T1‐weighted sequence with strong contrast between gray and white matter and minimal effect of B1 inhomogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…In the near future, systems of 12T and possibly even 20T (Budinger et al, 2016) will become available, offering the ability to visualize new features in resolution of about 0.1 millimeters (current 3T can capture about 1mm) (Budinger & Bird, 2017). Currently, use of 7T is well tolerated (Theysohn et al, 2008) and produces higher functional sensitivity in clinical studies, including pre-surgical planning (Beisteiner et al, 2011) as well as increased morphological specificity in Alzheimer’s disease (Nakada, Matsuzawa, Igarashi, Fujii, & Kwee, 2008), Parkinson’s disease (Cho et al, 2010), multiple sclerosis (Kollia et al, 2009; Metcalf et al, 2010), epilepsy (Veersema et al) and brain lesions (Moenninghoff et al, 2010; Tallantyre et al, 2009). Moreover, it will provide additional insight into neurotransmitter systems that are not easily resolved at lower field strengths (Cai et al, 2012; D.…”
Section: The Future Of Functional Neuroimagingmentioning
confidence: 99%